Challenging the Theory of Justice of All Companions: Elaboration of M. Syuhudi Ismail's Thought in the Book of Validity Methods of Hadith Sanad (Journal of Namibian Studies : History Politics Culture, 2023)
This paper aims to portray and position M. Syuhudi Ismail's thought among the scholars of hadith criticism and show his contribution to hadith studies in general. The focus of this article is on M. Syuhudi Ismail's views in the scholarly debates by analyzing the arguments in his works. There are two fundamental questions to uncover M. Syuhudi Ismail's views: first, were all companions fair or just, so there is no need to scrutinize them? and second, did the justice of the companions automatically guarantee the authenticity of the hadith sanad? Through descriptive-analytical method with reference to the typology of hadith critics in the science of al-jarh wa al-ta'dil, namely mutasyaddid, mutawasit, and mutasahil, this study concludes that M. Syuhudi Ismail takes the middle path regarding the justice of the companions. Through a review of the arguments between the two fortress, according to him, not all of the Prophet's companions are just as mutasahil scholars, but not all of them are rejected as mutasyaddid scholars. In this case, research is needed on individual narrators at the Companion level. Furthermore, if it is proven to be fair or just, the companions still need to be researched related to their kedhabitan. Such a view shows that M. Syuhudi Ismail is a moderate scholar (mutawasit) and remains critical in conducting sanad research at all levels.